2011
DOI: 10.1128/aac.01496-10
|View full text |Cite
|
Sign up to set email alerts
|

A New Small Molecule Specifically Inhibits the Cariogenic Bacterium Streptococcus mutans in Multispecies Biofilms

Abstract: Streptococcus mutans is a major cariogenic bacterium. It has adapted to the biofilm lifestyle, which is essential for pathogenesis of dental caries. We aimed to identify small molecules that can inhibit cariogenic S. mutans and to discover lead structures that could give rise to therapeutics for dental caries. In this study, we screened a focused small-molecule library of 506 compounds. Eight small molecules which inhibited S. mutans at a concentration of 4 M or less but did not affect cell growth or biofilm f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
101
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 46 publications
2
101
0
Order By: Relevance
“…However, brushing and flossing are neither practical nor accessible for many individuals, as they lack the knowledge, skills, or motivation (Cummins 2013). On the other hand, the consistent use of broad-spectrum antibiotics, which kill or inhibit the growth of planktonic bacteria, may disturb the body's microflora and lead to severe infections (Liu et al 2011).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…However, brushing and flossing are neither practical nor accessible for many individuals, as they lack the knowledge, skills, or motivation (Cummins 2013). On the other hand, the consistent use of broad-spectrum antibiotics, which kill or inhibit the growth of planktonic bacteria, may disturb the body's microflora and lead to severe infections (Liu et al 2011).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…However, few of these treatments have been proven to confer selectivity against S. mutans biofilms. In recent years, targeted antimicrobials capable of selectively eliminating S. mutans have been designed to achieve targeted killing with a minimal effect on other oral microbes (18)(19)(20), opening up alternative methods to prevent caries without disturbing the ecological balance between pathogens and commensal bacteria in the oral cavity.…”
mentioning
confidence: 99%
“…Several studies have indicated that the extent of Candida albicans biofilm detachment and detached-cell viability are dependent on the types of antimicrobials employed (26) and that detached cells gain enhanced adherence abilities (25). Given the breadth of the detrimental effects caused by biofilms and biofilm-detached cells, there have been significant efforts to develop and find agents controlling biofilm detachment and decreasing pathogenicity and viability of biofilm-detached cells (11,15).…”
mentioning
confidence: 99%
“…In addition, the effect of the antimicrobials on S. mutans biofilm structures was assessed using confocal laser scanning microscopy (CLSM) (15,17). Biofilm thickness and live/dead cell ratios were calculated using COMSTAT software.…”
mentioning
confidence: 99%